Nas trincheiras de combate, o abatimento: adicção e AIDS - MIRANDA, Alex Nazareno Ferreira de (Universidade Federal do Pará, 2014)
After three decades of the emergence of AIDS in the world, we are still speechless in the face of a dreaded disease to be pronounced by the weight of his name brings death. The disease, which emerged as a curse for sexual minorities, sex workers and drug users, printed on their bodies and their souls the symbol of immediate death, shameful and painful. Throughout this journey, his body had viral "imaged" by medical science that could not be removed from the mathematization that AIDS equals death, which would reduce the status of "a disease". This dissertation intends to provide an overview of AIDS, pointing out their appearance, the identification of the virus and the metaphors used for positioning of the disease in biological and moral locus of the modern world. We used metaphors of stigmatizing diseases, passed on places of care, to present the University Hospital João de Barros Barreto as a space marked by the stigma of TB and AIDS, which gives the image of horror to the people of Para . In this space, we met people whose helplessness and dependency relationships to an object/act external to the ego can have them brought to exposure to HIV. Of these, it was pointed to a case study of this phenomenon. In an attempt to understand the relationship with the object of addiction, were sought mainly Winnicottian the concepts of "environment maternante good enough", "transitional object" beyond "addiction", worked by Joyce McDougall. With the work done, it was observed that the gap reported in psychotherapy, very present in patients, is surrounded by addictive relationships, as a defense mode which lets you take the object as a replacement external breast vital. To listen to these dependences, we used the clinical perspective of Winnicott, with the possibility of repositioning the patient to modify their internal and external reality from a creative act.